The Influence of Islamic Social Reporting Disclosure and Islamic Corporate Governance on Financial Performance In Islamic Commercial Banks - Suriyanti, Suriyanti; Willy Siska; Ikram Saprillah; Isran Sutoyo; Nursanti Dwi Oktavia; Dewi Ratnasari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study aims to determine the effect between Islamic Social Reporting Disclosure and Good Corporate Governance on financial performance. The research method used is quantitative research. The object of this research is Islamic commercial banks registered with OJK in 2020-2022. The sample selection used purposive sampling method with a total sample of 13 Islamic commercial banks. The data in this study used secondary data obtained from the Financial Services Authority website and the websites of each Islamic commercial bank. The analysis technique used is multiple linear regression analysis using the Statistical Package for Social Science (SPSS) for Windows 25 software application. The results of this study indicate that Islamic Social Reporting Disclosure has a positive and significant effect on financial performance, where the more Islamic Social Reporting Disclosure increases, financial performance increases and Good Corporate Governance has a positive and significant effect on financial performance, where the more Good Corporate Governance increases, financial performance increases.